Assessment of ultimate bearing capacity of the pile for jacking & rotary piling method - Hassan, Nor Syamira; Ibrahim, Aniza; Alias, Rohaya; Abang Hasbollah, Dayang Zulaika; Ramli, Ahmad Bukhari (Elsevier, 2022)
Techniques of pile installation such as jacking, dropping weight, vibration, and explosion were applied but these methods were discovered to have weaknesses, such as high friction resistance and high settlements. To overcome these problems, this study introduces new method of pile installation which is Jacking and Rotary method (J&R). The objective of this study is to determine pile behaviour for static load test using common method namely jacking (J), and a new method, J&R through the ultimate pile capacity achieved by both methods. A stainless steel 25 mm circular pile, a 50 mm circular pile and a screw pile were used as test piles for this investigation. To achieve the objectives, this study employed graphical methods such as Brinch Hansen 80% and Tangent method to determine the ultimate pile capacity for both piling installation methods. Results revealed that for jacking method, the highest ultimate pile capacity value for the 50 mm circular pile was 1.186 kN, whereas the 25 mm circular pile had the lowest pile capacity reading of 0.539 kN. Screw pile shows the reading of 1.068 kN for its pile capacity. While for J&R, the highest average for both graphical methods are screw pile with 0.683 kN, while the 50 mm circular pile produced the lowest pile capacity which was 0.491 kN. For 25 mm, pile capacity using J&R is 0.543 kN. Result shows the acceptable for J&R methods to be introduced with further investigation such as the response of pile under axial loading and others.